2019
DOI: 10.1111/bph.14876
|View full text |Cite
|
Sign up to set email alerts
|

Enriching cancer pharmacology with drugs of marine origin

Abstract: Marine natural products have proven, over the last half-century, to be effective biological modulators. These molecules have revealed new targets for cancer therapy as well as dissimilar modes of action within typical classes of drugs. In this scenario, innovation from marine-based pharmaceuticals has helped advance cancer chemotherapy in many aspects, as most of these are designated as first-in-class drugs. Here, by examining the path from discovery to development of clinically approved drugs of marine origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 150 publications
(286 reference statements)
0
74
0
1
Order By: Relevance
“…Indeed, the Salinispora have attracted much attention as these obligate marine bacteria house unique biosynthetic pathways and, therefore, are a prolific spring of natural products [151]. Specifically, the species S. tropica is the producer of marizomib, a b-lactone-g-lactam proteasome inhibitor that is currently undergoing phase III clinical trials for the treatment of glioblastoma and multiple myeloma [14]. Following this hint, further studies then confirmed the occurrence of Salinispora sp.…”
Section: Further Accessing Brazilian Marine Environments: Studies Witmentioning
confidence: 97%
See 3 more Smart Citations
“…Indeed, the Salinispora have attracted much attention as these obligate marine bacteria house unique biosynthetic pathways and, therefore, are a prolific spring of natural products [151]. Specifically, the species S. tropica is the producer of marizomib, a b-lactone-g-lactam proteasome inhibitor that is currently undergoing phase III clinical trials for the treatment of glioblastoma and multiple myeloma [14]. Following this hint, further studies then confirmed the occurrence of Salinispora sp.…”
Section: Further Accessing Brazilian Marine Environments: Studies Witmentioning
confidence: 97%
“…From the natural products perspective, ascidians are among the best-studied groups and evidence has shown them, and their associated microorganisms, to abound in inventive chemistry with interesting bioactivity [80,81]. Three ascidian-sourced molecules have made it all the way to the clinics and figure among the list of drugs available for cancer treatment (reviewed by [14]). Trabectedin (ET-743), a peculiar kind of DNA alkylator, is an alkaloid obtained from Ecteinascidia turbinata Herdman, 1880 (Perophoridae) and the active principle of Yondelis, a chemotherapeutic agent used for treating soft tissue sarcoma since 2007 [82,83].…”
Section: Ascidiansmentioning
confidence: 99%
See 2 more Smart Citations
“…Didemnins A-C (19-21) ( Figure 11) were initially identified from ascidian symbiotic microbes. Among them, didemnin B (20), with a high cytotoxicity activity, was the first marine natural product to be utilized in clinical trials [64].…”
Section: Didemninsmentioning
confidence: 99%